Księga Rodzaju 12–50 w Qumran: interpretacja opowiadań o patriarchach w wybranych tekstach z Pustyni Judzkiej - Parchem, Marek (Collectanea Theologica, 2019)
The popularity that the Book of Genesis enjoyed among the members of the Qumran community (28 or more copies) undoubtedly accounted for the great number of the works inspired by its content that functioned as the paraphrase of the biblical material. Hence, in the scrolls interpreting the narrative of Gen 12–50 there were found in the Dead Sea Scrolls there are relatively many references and allusions to the patriarchs Abraham, Isaac and Jacob. Unfortunately, most of the texts – apart from the Genesis Apocryphon (1QapGen) – survived in a very fragmentary state only, therefore their interpretation meets serious difficulties and any conclusions should be drawn with the extreme cautiousness. Nevertheless, it can be acknowledged that, in many cases, the authors of the Qumran texts paraphrasing Gen 12–50, on the one hand enriched the biblical material with new elements by extending and supplementing it and, on the other hand, as in the biblical narratives of Gen, portray the patriarchs in a standard sequence listing their names (i.e. Abraham – Isaac – Jacob) in the context of the covenant and of the divine promises, and present them as the models of obedience, loyalty and faithfulness to God.